Tumour promoter activity in Malaysian Euphorbiaceae. - Norhanom, A.W.; Yadav, M. (Nature Publishing Group, 1995)
Herbal medication has been practised by the rural Malaysian Malays for a long time. However, the long-term side-effects have never been studied. In the present study, 48 species of Euphorbiaceae were screened for tumour-promoter activity by means of an in vitro assay using a human lymphoblastoid cell line harbouring the Epstein-Barr virus (EBV) genome. Twenty-seven per cent (13 out of 48) of the species tested were found to be positive, and in four species, namely Breynia coronata Hk.f, Codiaeum variegatum (L) Bl, Euphorbia atoto and Exocoecaria agallocha, EBV-inducing activity was observed when the plant extracts were tested at low concentrations of between 0.2 and 1.2 micrograms ml-1 in cell culture. This observation warrants attention from the regular users of these plants because regular use of plants with tumour-promoting activity could well be an aetiological factor for the promotion of tumours among rural Malaysian Malays.